Multilevel wavelet decomposition watermarking techniques - Wan Adnan, Wan Azizun (Federation of Engineering Institutions of Islamic Countries, 2006)
The merging of computer and communication technologies offers substantial new opportunities for processing and distribution of digital media. Along with powerful software and new devices such as digital cameras, scanners and printers, duplication, distribution, creation, and manipulation of images can be easily and cheaply done. The protection of ownership and the prevention of unauthorized tampering of images are becoming increasingly important concerns to multimedia content owners especially when the content is to be made available through the internet, which is unsecured. Digital watermarking is considered by many a potential solution to this problem. It is a process which embeds some characteristics data in an image in advance which later can be extracted that can be used for authentication or proof of ownership. This paper proposed a combination of spread spectrum encoding of the embedded message and wavelet transform-based invariants for digital image watermarking. Using the proposed method, we investigated the effect of using different values of gain factor at different sub-band of decomposition in such a way that it will not affect the perceptual transparency of the original image. The experimental results show that the imperceptibility and robustness are guaranteed using the proposed technique.